The Cultural Transmission of Environmental Preferences: Evidence from International Migration - Anastasia Litina; Simone Moriconi; Skerdilajda Zanaj (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
This paper investigates both theoretically and empirically the hypothesis that individual environmental attitudes can be partly accounted for by a cultural component. To empirically identify this component, we exploit variation associated with international migration ows. We find that the environmental attitudes of migrants, while being resilient to environmental conditions, also embed a cultural component, which persists till the second generation migrants. Our results suggest that, in the presence of multiple environmental problems that require collective action, comprehending the driving forces behind the formation of an environmental culture is critical to design effective policies.
Keywords: Q50; Q58; R23; 330; Cultural Transmission; Migration; Environmental Preferences